The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1038/sj.bjc.6601570
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous differentiation features associated with hormonal escape in a human prostate cancer xenograft

Abstract: Many theories mention hypersensitive, promiscuous, outlaw or bypass signalling pathways to explain the acquisition of hormone independence in prostate cancer. Hormonal escape of prostate tumours is marked by many biological changes, including mucinous and neuroendocrine differentiation. Since expression of several mucins has been linked to carcinoma tumour progression, we have characterised the expression of mucins at both RNA and protein levels in an in vivo model of prostate cancer in hormonal escape. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 33 publications
(46 reference statements)
0
17
0
1
Order By: Relevance
“…Alteration of tumour histology after docetaxel or docetaxel/trastuzumab combination treatment PAC120 and HID28 are high-grade adenocarcinomas that display similar differentiation with rare glandular structures, whereas HID25 is mucinous as previously described (Legrier et al, 2004) (Figure 2A, D and G). Mitoses were numerous in all tumours (mitotic index was 21, 8 and 11% in PAC120, HID25 and HID28, respectively).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Alteration of tumour histology after docetaxel or docetaxel/trastuzumab combination treatment PAC120 and HID28 are high-grade adenocarcinomas that display similar differentiation with rare glandular structures, whereas HID25 is mucinous as previously described (Legrier et al, 2004) (Figure 2A, D and G). Mitoses were numerous in all tumours (mitotic index was 21, 8 and 11% in PAC120, HID25 and HID28, respectively).…”
Section: Resultsmentioning
confidence: 77%
“…Reverse transcription of RNA was performed by random priming (cDNA cycle Kit, Invitrogen) using 2 mg of total RNA. Real-time RT -PCR and the design of primers were as described (Legrier et al, 2004). Primers designed with the Primer Express software (ABI, Les Ulis, France) were the following: AR: S: CTTGTGTCAAAAGCGAAATGGGC, AS: CA AAACATGGTCCCTGGCAGTC; HER2: S: TGGAGACCCGCTGAA CAATAC, AS: CCTTTCAAGATCTCTGTGAGGCTT; HPRT: S: GCTTTCCTTGGTCAGGCAGTATAA, AS: AAGGGCATATCCTA CAACAAACTT.…”
Section: Real-time Reverse Transcription (Rt) -Polymerase Chain Reactmentioning
confidence: 99%
“…There are reports on the dysregulated mucin gene expression in prostate cancer [32,33]. In previous studies, we have shown that MUC4 is aberrantly expressed in pancreatic cancer and pancreatic intraepithelial neoplastic lesions (PanINs), and its expression correlates with the disease progression [21,25].…”
Section: Discussionmentioning
confidence: 99%
“…However, in cancer cells and during progression, the mucin molecule becomes altered. Recently, it was reported that mucinous differentiation features are associated with hormonal escape in a human CaP xenograft model [3]. Mucins have also been implicated in the pathogenesis of benign and malignant diseases of secretory epithelial cells.…”
Section: Introductionmentioning
confidence: 99%